Altitude’s effects on complex cognitive ability - León, Federico R. (2013)
The coastal prejudice on the intelectual inferiority of Andean populations has been examined in scientific fora of Peru and abroad during the 19th and 20th centuries, but has not been systematically addressed by Peruvian psychology. Predictions were derived in this study from observations on cognitive effects of poor oxigenation, several evolutionary theories on cold and intelligence, and the theory of intelectualimpacts of UVB radiation and vitamin D3. The hypotheses were evaluated at both sides of the Andean mountains within a latitudinal segment (8º to 10º S) by analyzing mathematics and reading comprehension scores of children in 2nd grade of primary instruction from the 2 011 Control Sample of the Ministry of Education (N = 25 058). The findings strongly suggest that, if deficits in complex cognitive ability occur, they only affect persons not adapted to altitude.